Fasting-mimicking diet enhances EGFR-TKI efficacy in oral cancer through dual mechanisms: direct cancer cell sensitization and tumor-associated macrophage crosstalk - Wang, Lei; Wang, Yu-jie; Wang, Rong; Gong, Fu-lian; Chen, Ji-Yuan; Yu, Ya-ting; Qiu, Ze-rong; Yuan, Yong-fang (Frontiers in Pharmacology, 2025)
BackgroundEmerging evidence suggests the fasting-mimicking diet (FMD) offers a promising alternative to traditional calorie restriction and intermittent fasting, mitigating associated adverse effects including cachexia. Clinical trials have demonstrated the safety and efficacy of FMD, highlighting its considerable potential for translational applications. Future research should focus on assessing with molecularly targeted therapies to enhance therapeutic outcomes. The present study investigates the efficacy of FMD combined with EGFR-TKI therapy in oral cancer.MethodsM2-polarized macrophages derived from THP-1 cells were used to model TAMs. 2D and 3D oral cancer cell cultures (Cal-27 and OECM-1) were treated with gefitinib under standard or FMD-conditioned media. TAMs recruitment and interaction with tumor spheroids were assessed via co-culture and Transwell assays. Cal-27 xenograft mouse model was used to evaluate in vivo effects of FMD and gefitinib. Gene expression and signaling pathways were analyzed through bioinformatics, ELISA, RT-PCR, Western blot, and immunohistochemistry.ResultsFMD enhanced the anti-proliferative effect of gefitinib in vitro in both 2D and 3D oral cancer models directly. Bioinformatics and 3D models identified CCL2 as a gefitinib-induced chemokine reversed by FMD, which suppressed CCL2-mediated TAMs recruitment and tumor spheroid growth. In vivo, combined FMD and gefitinib treatment significantly reduced tumor volume, Ki-67+ proliferating cells, and M2-like TAMs density, accompanied by decreased serum CCL2 levels. Mechanistically, FMD inhibited gefitinib-induced STAT3 phosphorylation, leading to reduced CCL2 expression. Pharmacological modulation of STAT3 confirmed its role in regulating CCL2 secretion.ConclusionIn this study, we confirmed that fasting-mimicking diets not only directly enhances the sensitivity of oral cancer cells to gefitinib but also indirectly improves efficacy by attenuating CCL2-mediated TAMs recruitment under the gefitinib treatment environment. This study may provide a drug combination strategy and theoretical basis for the treatment of oral cancer, as well as scientific evidence for the clinical application of fasting-mimicking diets.